2008
DOI: 10.1111/j.1365-3059.2007.01739.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation in Nordic populations of Phytophthora infestans in 2003

Abstract: A total of 743 single-lesion isolates of Phytophthora infestans were collected in summer 2003 from Denmark, Finland, Norway and Sweden. Most of the isolates were tested for mating type, and subsets were tested for sensitivity to fungicides and virulence (host specific pathogenicity). Approximately 60% of the isolates were A1 mating type in each country. Both mating types were present in 40% of the fields where more than one isolate was tested, indicating strong potential for sexual reproduction. The proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
47
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 29 publications
7
47
2
Order By: Relevance
“…On the whole, the P isolates tested in this study showed 100 % of virulent forms against R1, R3, R4, R7, R10, and R11 and frequent presence of virulence against R5, R6, and R8 differentials. Meanwhile, virulence spectrum data for 4584 European isolates sampled for two decades as part of the Eucablight project (www.eucablight.org) and for 743 isolates sampled in 2003 in four Nordic countries (Lehtinen et al 2008) showed similar tendencies to our data.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…On the whole, the P isolates tested in this study showed 100 % of virulent forms against R1, R3, R4, R7, R10, and R11 and frequent presence of virulence against R5, R6, and R8 differentials. Meanwhile, virulence spectrum data for 4584 European isolates sampled for two decades as part of the Eucablight project (www.eucablight.org) and for 743 isolates sampled in 2003 in four Nordic countries (Lehtinen et al 2008) showed similar tendencies to our data.…”
Section: Discussionsupporting
confidence: 64%
“…Note that Polish P isolates had a higher value of C i than C p , indicating that the most complex races were predominant among the most common pathotypes. Similarly to other studies in the literature, rare virulence factors (e.g., against R9) in highly complex pathotypes were observed (Andrivon 1994;Andrivon et al 1994;Lehtinen et al 2008). The pronounced presence of highly complex pathotypes in a recent potato-infecting P. infestans population could be the result of sexual reproduction of the pathogen in Poland (Chmielarz et al 2014).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Therefore, the effect of mancozeb together with a residual effect of prior applications of fungicides may counteract the higher degree of insensitivity to metalaxyl within the population. During the 1990s metalaxyl resistance was associated with the A1 mating type in many European countries (Gisi and Cohen 1996;Day et al 2004;Lehtinen et al 2008). In the present study, no association between mating type and metalaxyl sensitivity was found.…”
Section: Discussioncontrasting
confidence: 49%
“…In the present study, no association between mating type and metalaxyl sensitivity was found. Lehtinen et al (2008) postulated that sexual reproduction, if present, should break any associations unless the genes for resistance and mating type are closely linked. This hypothesis was extensively tested in P. infestans population studies in central Mexico by Grünwald et al (2001).…”
Section: Discussionmentioning
confidence: 99%